Pasture chemoscapes and their ecological services. Issue 2 (5th June 2019) - Villalba, Juan J; Beauchemin, Karen A; Gregorini, Pablo; MacAdam, Jennifer W
Abstract: Ruminant livestock-production systems are between a rock and a hard place; they are experiencing increasing societal pressure to reduce environmental impacts in a world that demands increased food supply. Recent improvements in the understanding of the nutritional ecology of livestock by scientists may help livestock producers respond to these seemingly contradictory demands. Forages are nutrition and pharmacy centers with primary (nutrients) and plant secondary compounds (PSC; pharmaceuticals, nutraceuticals), which can provide multiple services for the proper functioning of agroecosystems. Legumes with lower contents of fiber and higher contents of nonstructural carbohydrates, coupled with different types and concentrations of PSC (e.g., condensed tannins, terpenes), create a diverse array of chemicals in the landscape (i.e., the "chemoscape") with the potential to enhance livestock nutrition, health and welfare relative to foodscapes dominated by grasses and other conventional feeds. These PSC-containing plants may reduce methane emissions and nitrogen (N) excretion from animals while increasing animal growth rate compared with swards dominated by grasses, and provide meat quality that appeals to consumers. Condensed tannins from sainfoin and saponins from alfalfa and manure of cattle consuming these forages also reduce N mobilization in soils, reduce nutrient leaching, and increase plant-available N stores for future use. The challenge for future pastoral production systems is to design multifunctional spatiotemporal arrangements of forages with "ideal" chemical diversity for specific ecoregions, aiming to achieve sustainability while increasing production goals and improving ecosystem services. Thus, the objective of this review is to stimulate the quest for chemically and taxonomically diverse pastoral feeding systems that optimize overall productivity; reduce environmental impacts; and enhance livestock, soil, and human health.